Strong agostic-type interactions in ruthenium benzylidene complexes containing 7-azaindole based scorpionate ligands - Tsoureas, Nikolaos; Nunn, Joshua; Bevis, Thomas; Haddow, Mairi F.; Hamilton, Alex; Owen, Gareth R. (Dalton Transactions, 2011)
The complexes [Ru(Tai)Cl{=C(H)Ph}(PCy3)] (4) and [Ru( PhBai)Cl{=C(H)Ph}(PCy3)] (5) [where Tai = HB(7-azaindolyl)3 and PhBai = Ph(H)B(7-azaindolyl) 2] have been prepared and structurally characterised. The borohydride unit is located in the coordination site trans to the chloride ligand in both complexes. The degree of interaction between the borohydride group and the metal centre was found to be significantly large in both cases. Thermolysis reactions involving complex 4 led to a dehydrogenation reaction forming [Ru(Tai)Cl{PCy2(η2-C6H9)}] (6) where the benzylidene group acts as a hydrogen acceptor. © The Royal Society of Chemistry 2011.